Near-field optical properties of quantum dots, applications and perspectives - Zora, A.; Triberis, G.P.; Simserides, C. (Recent Patents on Nanotechnology, 2011)
Recent years have witnessed tremendous research in quantum dots as excellent models of quantum physics at the nanoscale and as excellent candidates for various applications based on their optoelectronic properties. This review intends to present theoretical and experimental investigations of the near-field optical properties of these structures, and their multimodal applications such as biosensors, biological labels, optical fibers, switches and sensors, visual displays, photovoltaic devices and related patents.